PERTANGGUNGJAWABAN NEGARA TERHADAP PEMEGANG HAK ATAS TANAH MUSNAH BERDASARKAN PASAL 15 PERATURAN MENTERI AGRARIA DAN TATA RUANG/ KEPALA BADAN PERTANAHAN NASIONAL NOMOR 17 TAHUN 2021 TENTANG TATA CARA PENETAPAN TANAH MUSNAH - Ni Kadek Evi Saraswati; I Kadek Dony Hartawan; Ni Komang Irma Sukmaningsih (Universitas Pendidikan Ganesha, 2026)
Land is an object of property rights that has important economic, social, and legal value for the community.However, the geographical conditions in Indonesia are often prone to natural disasters, which can cause land to change physically or be lost permanently.This results in the land being unable to be identified, used, or developed as it should be. The government is trying to provide legal certainty in this situation.Through Regulation of the Minister of Agrarian Affairs and Spatial Planning / Head of the National Land Office Number 17 of 2021 on the Procedures for Determining Lost Land, the government has set out how the status of lost land is determined, along with the legal basis, which includes removing the land rights.However, the regulation still raises important issues regarding the state's responsibility towards land rights holders who lose their rights. This rule only deals with the provision of religious funds to the land rights holders, but it does not explain what the funds are, how much they are, the basis for calculating them, the process of giving them, or who is responsible for distributing the money.